2011
DOI: 10.1088/0004-637x/737/2/60
|View full text |Cite
|
Sign up to set email alerts
|

REACTIONS OF COLD TRAPPED CH+IONS WITH SLOW H ATOMS

Abstract: The destruction of CH + ions in collisions with H atoms has been studied in a temperature-variable 22 pole ion trap (22PT) combined with a cold effusive H-atom beam. The stored ions are relaxed to temperatures of T 22PT 12 K. The hydrogen atoms, produced in a radio frequency discharge, are slowed down to various temperatures of T ACC 7 K. They are formed into an effusive beam. The effective density of the hydrogen atoms in the trap as well as the H 2 background are determined in situ using chemical probing wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
64
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 46 publications
14
64
2
Order By: Relevance
“…(3) is shown in Figure 1 as the full line. This result is practically indistinguishable from the PST result [6], and is clearly in disagreement with the experiment [1] at low temperatures.…”
Section: Standard Statistical Modelcontrasting
confidence: 67%
See 2 more Smart Citations
“…(3) is shown in Figure 1 as the full line. This result is practically indistinguishable from the PST result [6], and is clearly in disagreement with the experiment [1] at low temperatures.…”
Section: Standard Statistical Modelcontrasting
confidence: 67%
“…Under these conditions, it would be expected that at low collision energies the reaction would proceed via the formation of a long-lived complex, in which case, the application of standard statistical models (see for example [2][3][4][5] and references therein) should give a reasonable prediction of the reaction rate coefficient. Indeed, one such model based on phase space theory (PST) has been applied [6] to reaction (1) and the resulting rate coefficient at low temperatures approaches a constant Langevin value of k = 1.98 Â 10 À9 cm 3 s À1 , clearly in contrast to the rapid decrease of the measured rate coefficient [1]. Neither quasi classical trajectory (QCT) calculations [6,7] nor quantum mechanical methods [7,8] using the full PES provide a satisfactory explanation of the experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasil et al 5,6 have found a similar behaviour. They measured abstraction cross sections which have a strong gradient for temperatures less than 50 K. The rate at 12.2 K, for example, is about 5 · 10 −11 cm 3 s −1 .…”
Section: Rate Coefficientsmentioning
confidence: 63%
“…This potential was used by Halvick et al 4 for quasi classical trajectory (QCT) and phase space theory (PST) analysis of the H + CH + reaction. The C + abstraction cross sections are predicted to be monotonically decreasing between 1 K and 1000 K. New measurements of Plasil and Gerlich [5][6][7] show a maximum of the rate coefficient at 60 K and a strong gradient of the thermal rate for lower temperatures, which diverges from theoretical results 3,4 . This discrepancy of experiment and theory and the unexplained abundance of CH + in interstellar environments motivate further research.…”
Section: Introductionmentioning
confidence: 86%